Therapeutic Potential and Clinical Evidence of Hesperidin as Neuroprotective Agent - Joshi, Shivanki; Dhingra, Ashwani K.; Chopra, Bhawna; Guarve, Kumar; Bhateja, Deepak (Central Nervous System Agents in Medicinal Chemistry, 2022)
Background: Neuroprotection is preserving neural function in various neurodegenerative diseases like Alzheimer’s, Huntington’s, Parkinson’s, and multiple sclerosis. Hesperidin, a flavanone glycoside in citrus fruits such as sweet oranges and lemons, possesses many biological effects, including neuroprotection. Objective: The study aims to explore the neuropharmacological mechanisms and therapeutic potential of hesperidin in the management of neurodegenerative disorders. Methods: It emphasizes comparative and clinical trial studies with a number of targets reviewed from the data available on PubMed, Science Direct, Clinicaltrails.gov, and from many reputed foundations. Results: Escalating clinical evidence has established the inhibitory effect of hesperidin in the management of neurodegenerative disorders. Neuroprotective potential of hesperidin is characterized by endogenous antioxidant defence functions, improvement of neural growth factors, antineuroinflammatory activity, and apoptotic pathways. Conclusion: The present study highlights the beneficial neuropharmacological potential of hesperidin, including anticonvulsant, antidepressant, antioxidant, anti-inflammatory, memory, and locomotor enhancing activities.
Keywords: Hesperidin